2020
DOI: 10.1371/journal.pone.0241152
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of endoscopic and microscopic inlay butterfly cartilage tympanoplasties and their educational utility

Abstract: Objectives Inlay butterfly cartilage tympanoplasty (IBCT) is a simple grafting technique. Endoscopy facilitates visualization by eliminating blind spots. We analyzed the outcomes of IBCT using both endoscopic and microscopic approaches, and assessed how trainees perceived the educational opportunities afforded. Materials and methods Sixty patients who underwent IBCT were allocated to Group I (n = 30; microscopic IBCT) and Group II (n = 30; endoscopic IBCT) by the dates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…14 Hashim et al (2020) 40 Retrospective Endoscopic and microscopic IBCT were associated with good success rates. The endoscopic approach facilitates visualization, and a better understanding of the middle ear anatomy and the required surgical steps.…”
Section: Resultsmentioning
confidence: 98%
“…14 Hashim et al (2020) 40 Retrospective Endoscopic and microscopic IBCT were associated with good success rates. The endoscopic approach facilitates visualization, and a better understanding of the middle ear anatomy and the required surgical steps.…”
Section: Resultsmentioning
confidence: 98%
“…Twenty‐eight studies were included in accordance with the eligibility criteria (Table II). 4,8,10,14–38 Primary population sizes ranged from a single individual, featured in 10 studies, 4,15,20,23,24,27,29,30,32,34 up to a maximum of 70 included in Denton et al (2022) 37 . The most popular study design was retrospective, 12 of which were included 4,10,15,16,23,27–30,32,34,36 .…”
Section: Resultsmentioning
confidence: 99%
“… 4,8,10,14–38 Primary population sizes ranged from a single individual, featured in 10 studies, 4,15,20,23,24,27,29,30,32,34 up to a maximum of 70 included in Denton et al (2022) 37 . The most popular study design was retrospective, 12 of which were included 4,10,15,16,23,27–30,32,34,36 . Quality assessment resulted in five “good,” 19 “fair” and four “poor” ratings (Appendix S3).…”
Section: Resultsmentioning
confidence: 99%
“…The results were confirmed by others. 7 - 13 A randomized clinical trial comparing this technique with underlay fascia tympanoplasty demonstrated similar efficacy in graft take and audiometric outcomes, with advantages of the butterfly in terms of ease and speed of execution and better recovery (instant hearing recovery, less postoperative care, and less pain), making it a cheaper procedure for the health system. 14 …”
mentioning
confidence: 99%
“…The results were confirmed by others. [7][8][9][10][11][12][13] A randomized clinical trial comparing this technique with underlay fascia tympanoplasty demonstrated similar efficacy in graft take and audiometric outcomes, with advantages of the butterfly in terms of ease and speed of execution and better recovery (instant hearing recovery, less postoperative care, and less pain), making it a cheaper procedure for the health system. 14 The objective is to carry out a systematic review and metaanalysis of studies that compared the effectiveness of butterfly cartilage inlay tympanoplasty (BCIT) with traditional temporal fascia underlay tympanoplasty (TFUT) and, with the increase in statistical power conferred by this methodology, to identify whether there is a difference in anatomic and/or functional efficacy between the techniques and whether there are predictive factors for success.…”
mentioning
confidence: 99%